The Safety of Using Body-Transmit MRI in Patients with Implanted Deep Brain Stimulation Devices. - Joshua Kahan; Anastasia Papadaki; Mark White; Laura Mancini; Tarek Yousry; Ludvic Zrinzo; Patricia Limousin; Marwan Hariz; Tom Foltynie; John Thornton (PLoS ONE)
Background Deep brain stimulation (DBS) is an established treatment for patients with movement disorders. Patients receiving chronic DBS provide a unique opportunity to explore the underlying mechanisms of DBS using functional MRI. It has been shown that the main safety concern with MRI in these patients is heating at the electrode tips - which can be minimised with strict adherence to a supervised acquisition protocol using a head-transmit/receive coil at 1.5T. MRI using the body-transmit coil with a multi-channel receive head coil has a number of potential advantages including an improved signal-to-noise ratio. Study outline We compared the safety of cranial MRI in an in vitro model of bilateral DBS using both head-transmit and body-transmit coils. We performed fibre-optic thermometry at a Medtronic ActivaPC device and Medtronic 3389 electrodes during turbo-spin echo (TSE) MRI using both coil arrangements at 1.5T and 3T, in addition to gradient-echo echo-planar fMRI exposure at 1.5T. Finally, we investigated the effect of transmit-coil choice on DBS stimulus delivery during MRI. Results Temperature increases were consistently largest at the electrode tips. Changing from head- to body-transmit coil significantly increased the electrode temperature elevation during TSE scans with scanner-reported head SAR 0.2W/kg from 0.45°C to 0.79°C (p<0.001) at 1.5T, and from 1.25°C to 1.44°C (p<0.001) at 3T. The position of the phantom relative to the body coil significantly impacted on electrode heating at 1.5T; however, the greatest heating observed in any position tested remained <1°C at this field strength. Conclusions We conclude that (1) with our specific hardware and SAR-limited protocol, body-transmit cranial MRI at 1.5T does not produce heating exceeding international guidelines, even in cases of poorly positioned patients, (2) cranial MRI at 3T can readily produce heating exceeding international guidelines, (3) patients with ActivaPC Medtronic systems are safe to be recruited to future fMRI experiments performed under the specific conditions defined by our protocol, with no likelihood of confound by inappropriate stimulus delivery.